2022
DOI: 10.3390/joitmc8040187
|View full text |Cite
|
Sign up to set email alerts
|

Driving Innovation Initiatives in a Multinational Company Subsidiary: A Case Study and Conceptual Framework for Further Application

Abstract: This study aims at identifying factors that facilitate the development of the capacity to generate innovations in a subsidiary of a multinational company. Based on the understanding that innovation management deals with the establishment of organizational routines and the investigation of environmental factors that affect the success of the innovation process, the purpose of this work is to contribute toward identifying these factors. For this, a single case study was carried out in a Brazilian subsidiary of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
0
1
Order By: Relevance
“…According to (Franco and Landini, 2022), management Rena: The role of innovation in making sustainable and future-ready businesses and the organizational practices are found to the important factors that drive innovation in a firm. In literature (Ribeiro et al, 2022), the authors assessed the factors that support the development of capabilities in a company to innovate products/services. The study outcomes confirmed the existence of 20 factors that potentially drive the innovation process and are categorized under three domains such as induced factors, spontaneous factors, and reasons to innovate.…”
Section: Innovation In Business Practicesmentioning
confidence: 99%
“…According to (Franco and Landini, 2022), management Rena: The role of innovation in making sustainable and future-ready businesses and the organizational practices are found to the important factors that drive innovation in a firm. In literature (Ribeiro et al, 2022), the authors assessed the factors that support the development of capabilities in a company to innovate products/services. The study outcomes confirmed the existence of 20 factors that potentially drive the innovation process and are categorized under three domains such as induced factors, spontaneous factors, and reasons to innovate.…”
Section: Innovation In Business Practicesmentioning
confidence: 99%
“…Останні публікації серед зарубіжних науковців присвячено результатам досліджень щодо: інтеграції динамічних можливостей у відкриті інновації для підтримки фірм [4], особливостям процесу передачі технологій від співпраці між науковою сферою, промисловістю та урядами [5 ], розвитку регіональних інновацій [6], впливу технологічних інновацій на показники діяльності виробничих фірм [7], факторів, які сприяють розвитку інноваційного потенціалу компанії [8], впровадження екологічних інноваційних технологій для прискорення сталого розвитку обробної промисловості [9], факторного ефекту поєднання політики науково-технічних інновацій [10], впливу поєднання різних типів інновацій на ефективність підприємств [11].…”
Section: аналіз публікаційunclassified